Local modulation of electrical distributions in bent PS fibers via multi-segmented layered structures - Xu, Zelin; Fang, Kai; Wang, Tiqing; Li, Peng; Liu, Dianzi; Kuznetsova, Iren E.; Ma, Tingfeng; Qian, Zhenghua (Acta mechanica, 2023)
Piezoelectric semiconductor fibers are the foundation of nanogenerators, nano-force sensors, and other nanodevices. Regulating the local piezopotential characteristics inside the PS fiber is crucial for its piezoelectric performance. However, due to the extremely small size of nanofibers, this is quite challenging. In this study, we propose a method for modulating local electrical distribution of bent PS fibers using a multi-segmented layered structure. The field equations for bent PS fibers are derived, and the effect of a non-uniform additional layer’s discontinuity in material properties and thickness distributions on the distributions of strain, potential, and charge carrier concentration fields within the fiber are investigated. Results from theoretical studies and case studies indicate that the discontinuity of material coefficients or the thickness in the attached layer allows the local piezopotential distribution of the bent fiber to be effectively tuned by external forces. In the bent fibers, the potential and carrier concentration in the intermediate region no longer remain constant, but instead, localized potential wells and barriers, or plateau-like regions of high and low potential, start to form along the axial direction, and they are symmetric with respect to the strain neutral axis. The discontinuity of various material coefficients in the attached layer has different effects on the local potential changes in the bent fiber. Local potentials of arbitrary form can be controlled through different material and thicknesses distribution combinations of the attached layer. The findings of this study provide important guidance for modulating the local electrical distributions of PS fibers and offer new insights and design ideas for nanoscale piezoelectric devices.